Enhanced optical dichroism of graphene nanoribbons - Hipolito, Fábio (2012)
The optical conductivity of graphene nanoribbons is analytical and exactly derived. It is shown that the absence of translational invariance along the transverse direction allows considerable intraband absorption in a narrow frequency window that varies with the ribbon width, and lies in the THz range domain for ribbons 10–100 nm wide. In this spectral region the absorption anisotropy can be as high as two orders of magnitude, which renders the medium strongly dichroic, and allows for a very high degree of polarization (up to ∼85%) with just a single layer of graphene. Using a cavity for impedance enhancement, or a stack of few layer nanoribbons, these values can reach almost 100%. This opens a potential prospect of employing graphene ribbon structures as efficient polarizers in the far IR and THz frequencies.